TREN BUSANA MUSLIMAH DALAM PERSPEKTIF BISNIS DAN DAKWAH - Anafarhanah, Sri (UIN Antasari Banjarmasin, 2019)
Indonesia is a country whose majority is the largest Muslim in the world, making Muslim clothing the choice of most Muslim women in dress. This makes Muslim clothing in Indonesia continue to grow rapidly following the development of tren and fashions. In a business perspective, there are great opportunities that can be achieved by entrepreneurs in the field of domestic fashion to contribute to this development. Because of the fact, Muslim clothing is currently not only a fashion choice to cover aurat, but has become a life style for some Muslim women. With the many Muslim fashion fashions that are now being produced by domestic and foreign businessmen, this tren is increasingly in demand. Appearing in an Islamic and fashionable style makes Muslim women increasingly choose Muslim clothing. This closed clothing is not only worn by adult women but extends to teenagers and children. In line with this tren, in the perspective of da'wah, one of the aims of da'wah in upholding the amar ma'ruf nahi munkar can be helped as long as Muslim clothing is used in accordance with Islamic law, because basically the clothes that must be worn by Muslim women are clothes that cover their nakedness the limits specified in Islam.